An update on endotoxin neutralization strategies in Gram-negative bacterial infections. Issue 4 (3rd April 2021) - Brandenburg, Klaus; Schromm, Andra B; Weindl, Günther; Heinbockel, Lena; Correa, Wilmar; Mauss, Karl; Martinez de Tejada, Guillermo; Garidel, Patrick
ABSTRACT: Introduction: Gram-negative bacterial infections represent still a severe problem of human health care, regarding the increase in multi-resistance against classical antibiotics and the lack of newly developed antimicrobials. For the fight against these germs, anti-infective agents must overcome and/or bind to the Gram-negative outer membrane consisting of a lipopolysaccharide (LPS, endotoxin) outer leaflet and an inner leaflet from phospholipids, with additional peripheral or integral membrane proteins (OMP's). Areas covered: The current article reviews data of existing therapeutic options and summarizes newer approaches for targeting and neutralizing endotoxins, ranging from in vitro over in vivo animal data to clinical applications by using databases such as Medline. Expert opinion: Conventional antibiotic treatment of the bacteria leads to their killing, but not necessary LPS neutralization, which may be a severe problem in particular for the systemic pathway. This is the reason why there is an increasing number of therapeutic approaches, which – besides combating whole bacteria – at the same time try to neutralize endotoxin within or outside the bacterial cells mainly responsible for the high inflammation induction in Gram-negative species.